Neurological Symptoms Associated with Acute Multifocal Placoid Pigment Epitheliopathy: Treatment Dilemma and Diagnostic Issues. (May 2015) - Oleszczuk, Justyna D.; Saeed, Muhammad Usman
ABSTRACT Acute multifocal placoid pigment epitheliopathy (AMPPE) is thought to be caused by vasculitis of the choroid. Central nervous system involvement is rare. We report a case of a 28-year-old male who developed blurred vision (6/12 OD, 6/24 OS). Past medical history involved non-specific viral meningitis treated with intravenous antibiotics and antivirals. Subsequently, the patient complained of recurrent headaches. Based on typical clinical findings and fluorescein angiogram, he was diagnosed with AMPPE. Visual disturbance resolved without any systemic treatment. Six months later, visual symptoms recurred and resolved spontaneously, but his headache continued. A few months later, the patient developed acute progressive neurological signs and symptoms necessitating inpatient admission. Lacunar infarcts in the CNS were found, which had not been noted in previous neuro-imaging studies. Cerebral vasculitis associated with AMPPE was diagnosed and treated with systemic steroids and immune suppression. Currently, the patient remains asymptomatic under joined care of an ophthalmologist and a neurologist.